2014
DOI: 10.1080/19325037.2014.933139
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity Among Adults With Type 2 Diabetes: A Systematic Literature Review

Abstract: Background: Adults with type 2 diabetes (T2DM) tend not to regularly exercise. It is important to identify correlates associated with physical activity (PA) in this population to promote positive behavior change. Purpose: To conduct a systematic review to identify the biological, psychosocial, and environmental factors associated with PA behavior among adults with T2DM. Methods: Research articles were selected meeting the following criteria: adults ($ 18 years) with T2DM, PA as the dependent variable, and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
3
15
1
2
Order By: Relevance
“…Evidence on activity levels in populations with T2D is variable across countries. However, low levels of PA in T2D populations have been reported in several studies [ 15 ] including those from Arabic speaking countries [ 16 , 22 , 23 ]. Whilst meeting PA recommendations in this study is higher than national levels (15%), activity levels in the current study are much lower than those reported in populations with T2D in the UK (34%) [ 24 ] and USA (36 to 50%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on activity levels in populations with T2D is variable across countries. However, low levels of PA in T2D populations have been reported in several studies [ 15 ] including those from Arabic speaking countries [ 16 , 22 , 23 ]. Whilst meeting PA recommendations in this study is higher than national levels (15%), activity levels in the current study are much lower than those reported in populations with T2D in the UK (34%) [ 24 ] and USA (36 to 50%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meeting PA recommendations in travel and leisure domains was also seen to be more likely in younger individuals. Younger individuals in the current study have less comorbidities and hence may experience less discomfort compared to older aged individuals with T2D who might be concerned about their disease condition [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having diabetes as a significant predictor of a normal BMI is not supported by NHANES III data on adults with Type 2 diabetes that revealed 54.8% were obese (BMI = ≥30 kg/m 2 ), 31% reported no leisure time activity, and 38% did not meet physical activity recommendations [ 20 ]. The high level of health consciousness and health knowledge of the current study group may have impacted this finding given that physical activity can improve glycemic control and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has shown that BMI, sex, age, education and income are associated with physical activity in adults with type 2 diabetes, the evidence has been inconsistent. 27 For instance, some studies have reported that older age and female sex are negatively associated with physical activity, 12 while other studies suggest that age and sex 28 are unrelated to physical activity in adults living with diabetes. In terms of educational level, Hays et al 29 observed that those without a high school education were less likely to be physically active.…”
Section: Discussionmentioning
confidence: 99%